STUDENTS’ PERCEPTIONS OF ICE-BREAKING ACTIVITIES IN ENGLISH LANGUAGE LEARNING AT THE JUNIOR HIGH SCHOOL LEVEL - Marliasari, Sherly; Rositasari, Tri; Saputri, Kurnia; Jannah, Nurul (Universitas Muhammadiyah Palembang, 2026)
This study investigates eighth-grade students’ perceptions of ice-breaking activities in English language learning at SMPN 11 Palembang. Grounded in the need to enhance student motivation and classroom engagement in EFL contexts, the study employed a quantitative research design through survey approach. Data were collected through a closed-ended Likert-scale questionnaire administered to 34 eighth-grade students. The findings indicate that most students hold positive perceptions of ice-breaking activities, perceiving them as helpful in increasing learning focus, reducing classroom boredom, and creating a more supportive learning atmosphere. Students generally agreed that the use of ice-breaking activities contributes to more engaging English lessons and improves classroom dynamics. However, the findings are limited to students’ perceptions and do not claim direct effects on learning outcomes. The study underscores the pedagogical value of ice-breaking activities as a motivational strategy in English language classrooms and suggests their thoughtful integration into EFL instruction.